Tougher laws for party hopping, not vacating seat - Doksil, Mariah; Morpi, Murib (BorneoPost, 2014)
KOTA KINABALU: Leaders from opposition parties in Sabah do not agree with the proposal by political analyst Assoc Prof Dr Mohd Azizuddin Mohd Sani on the imposition of stiffer penalties on those elected representatives who vacated their seats without a valid reason. Mohd Azizuddin, has suggested that any elected representative who vacates his or her seat without a valid reason should be fined a minimum of RM1 million, bear the cost of holding a by-election and banned from holding public office for life"!